2021
DOI: 10.1001/jamaneurol.2020.4799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Investigation Findings, and Treatment Outcomes of Spontaneous Intracranial Hypotension Syndrome

Abstract: IMPORTANCE Spontaneous intracranial hypotension (SIH) is a highly disabling but often misdiagnosed disorder. The best management options for patients with SIH are still uncertain.OBJECTIVE To provide an objective summary of the available evidence on the clinical presentation, investigations findings, and treatment outcomes for SIH.DATA SOURCES Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline-compliant systematic review and meta-analysis of the literature on SIH. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
324
1
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(349 citation statements)
references
References 48 publications
7
324
1
17
Order By: Relevance
“…There are no guidelines widely acknowledged for the treatment of SIH yet. According to meta-analysis about SIH, conservative treatment including bed rest, hydration, analgesia, steroids, caffeine was effective in about 24.5% of 881 patients for a period ranging from 7 to 9 weeks [7,17]. EBP is commonly used treatment to patients showed no response to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are no guidelines widely acknowledged for the treatment of SIH yet. According to meta-analysis about SIH, conservative treatment including bed rest, hydration, analgesia, steroids, caffeine was effective in about 24.5% of 881 patients for a period ranging from 7 to 9 weeks [7,17]. EBP is commonly used treatment to patients showed no response to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though EBP is commonly used for the treatment of SIH, the process how it acts has not been determined, but may involve a temporary increase in epidural pressure, the sealing of a tear by coagulating injected blood, or the initiation of inflammatory reactions that promote dural tear healing [8,[10][11][12]. According to previous studies, the therapeutic effect of EBP showed various improvement rate in 64-93% of patients after first treatment [7,13,[18][19][20]. There are two methods of EBP, targeted and non-targeted one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations